Life on the edge: exploring the effects of urbanisation on the foraging ecology and ecotoxicology of caracals - Leighton, Gabriella Ruth Michaela (Department of Biological Sciences, 2022)
The continuing loss of natural habitat to a broad range of human activities is one of the main drivers of biodiversity decline worldwide and a defining feature of the Anthropocene. However, some opportunistic, generalist species may benefit from transformed landscapes through, for example, the absence of apex predators or access to human-subsidised food resources. These benefits may thus offset the higher mortality and health risks typically associated with human-dominated landscapes. To understand the cost-benefit trade-offs of life on the urban edge, I investigated the foraging ecology and ecotoxicology of a highly adaptable medium-sized carnivore, the caracal (Caracal caracal), utilising both natural and transformed landscapes around the rapidly growing city of Cape Town, South Africa. Through a combination of scat analysis (n = 654 scats) and prey remains located at 677 GPS clusters, I quantified dietary resource use of 26 collared individuals, as well as opportunistically sampled caracals. Using a range of gut transit times, I estimated whether scat at cluster sites was from the same or an earlier feeding event, thereby increasing the overall detection of individual-specific feeding events by > 50%. While most feeding events occurred within 200 m of the urban edge of Cape Town, I found that caracals have flexible diets that largely comprise medium- to small-sized wild prey (60%), followed by human-associated species (27%), and introduced or domestic species (13%). Using a subset of the feeding and resting events (n = 326 prey remains, n = 384 scat, n = 177 resting sites) that were associated with known individuals (n = 17), I then investigated caracal resource selection using both anthropogenic and environmental factors. Additionally, I examined the behaviour of caracal at feeding clusters to determine if they respond to spatial and temporal risks associated with anthropogenic factors. I found divergent resource selection patterns based on the level of exposure to urbanisation: caracals living in the urban-dominated region of the Peninsula (n = 14; 548 feeding events) select for the urban edge, while caracals in the wildland-dominated region (n = 3; 162 feeding events) strongly avoid it. I argue that in the more urbanised region, caracals forage on or close to the urban edge because this is where the remaining low-lying wildland habitat is most productive and attractive. Consequently, caracals in heavily transformed areas, which might otherwise tend to avoid human disturbance, have habituated to human presence but reduce their risk of detection by remaining cryptic, prolonging handling time, and maintaining high feeding site fidelity where cover is available. To quantify the consequences of peri-urban foraging, I use an ecotoxicological approach to assess environmental contamination and its potential effects on caracals. It is widely reported that persistent organic pollutants (POPs), including organochlorines (OCs) such as PCBs and DDT and its metabolites, are extremely toxic, causing adverse effects on wildlife and human health. I tested blood and adipose tissues of caracals, with different diets utilising a range of natural and transformed landscapes, for exposure to commonly detected OCs. Despite restrictions on their use, I found extensive OC burdens, with 100% of adipose samples exposed to both DDT and PCBs, and 100% and 83% of blood samples exposed to DDT and PCBs respectively. Caracals using areas with a higher density of people and electrical transformers, and those using areas close to informal settlements, had higher exposure to OCs. Additionally, the use of vineyards and wetlands and a diet with a greater proportion of higher trophic level or exotic prey correlated with a higher risk of exposure to OC pollutants. Full blood analyses revealed that exposure levels to OCs were also associated with higher counts of infection-fighting cells, suggesting these compounds may affect the immune response of individuals. With time, these detrimental effects may have population-level repercussions through impacts on reproductive success and fitness. Together these findings reveal that while caracals and other medium-sized adaptable carnivores may persist within or adjacent to human transformed habitats, they still prefer natural habitat and pay a significant cost for foraging on prey species that have been contaminated by pollutants associated with urban and rural land uses. Urban edges may thus be an ecotoxicological trap, threatening the health and long-term persistence of caracals and other wildlife in this and other biodiversity hotspots. Reducing environmental contamination and limiting habitat loss to urban sprawl would benefit wildlife living on the transformed edges but requires significant improvements to both the legislation governing pollutants and the spatial planning of cities.